Analisis Keterbukaan Diri Dalam Komunikasi Interpersonal Antara Santriwati Dan Ustadzah Dalam Pembentukan Karakter Santri Di Pondok Pesantren Modern Daarul Arqom Tulung - Azzahra, Nadhifa (Commed Jurnal Komunikasi dan Media, 2026)
Abstract Interpersonal communication plays an important role in the character building process of students at the Daarul Arqom Modern Islamic School in Tulung which occurs through the relationship between teachers and students. The approach used is a case study with descriptive qualitative analysis. Data processing follows the guideliness of Miles and Hubermans’s 1994 Interactive Analysis Model. The steps in this model include observation, interviews, and documentation. Several factors, including the psychological characteristics and personalities of students, hierarchical rules in Islamic Boarding school, snd limited time, contribute to the low level of self disclosure among these students According to Altman and Taylor’s Social Penetration Theory (1973), which describes how relationships develop through stags of self- disclosure, interpersonal communication generally takes place in a formal manner and does not touch on emotional aspects. The success of this program depend on the mental readiness of the students snd the empathy skills of the teacher. However, the SEMEDI (One Night at the Ma’had) program initiative actually creates opportunities to build closer relationships. In order to optimize student character development, this study emphasizes the need to strengrhen a dialogical and supportive communication strategy approach Keywords: : Interpersonal Communication, Self-Disclosure, Students and Female Teachers